The Analysis Of Determinants Of Regency/City Minimum Wages In The Pekalongan Residency On 2017-2022 - Fitriani, Citra Indah; Nurhayati, Siti Fatimah (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
The minimum wage is a method of achieving a reasonable income for workers by enhancing their well-being while not neglecting increases in productivity, firm progress, and overall economic development. The purpose of this study is to look into the effects of the human development index (HDI), labor force participation rate (TPAK), inflation, and investment on the minimum wage in the Pekalongan Residency's regencies/cities between 2017 and 2022. The study uses secondary data in the form of panel data, which includes cross-sectional data from 7 regencies in the Pekalongan Residency as well as time-series data from 2017 to 2022. The Fixed Effect Model (FEM) serves as the methodological framework. The study's findings revealed that the human development index and investment have a positive and significant influence on minimum wages in the regencies/cities of Pekalongan Residency, refuting the original hypothesis. In contrast, labor force participation and inflation have a negative impact on minimum salaries in the district/city of Pekalongan Residency. The F-test findings corroborate the model's existence, with an R-squared value of 0.9384, showing that HDI, TPAK, Inflation, and Investment account for 93.84% of the variation in the regency/city minimum wage in Pekalongan Residency. The remaining 6.16% is due to other variables not included in the model. Keywords: Regional Minimum Wages, Human Development Index, Labor Force Participation Rate